Utility of 18F-FDG PET/CT for diagnosing and staging solitary malignant tumors of the spleen - Shao, Mingyan; Xu, Rong; Fan, Sisi; Qi, Wanling (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the diagnostic and staging value of 18F-FDG PET/CT in solitary malignant tumors of the spleen (SMTS).MethodsWe retrospectively analyzed clinical data, 18F-FDG PET/CT and contrast-enhanced CT findings from 25 pathologically confirmed SMTS cases. The PET/CT characteristics including lesion distribution, accompanying signs, maximum standardized uptake value (SUVmax), and pathological types were analyzed, with comparison of diagnostic and staging efficacy between PET/CT and contrast-enhanced CT.ResultsAll 25 SMTS cases showed FDG uptake on PET/CT: mild uptake in 2 cases (SUVmax 2.4 and 2.3 respectively), moderate uptake in 8 cases (SUVmax 6.4 ± 3.5), and intense uptake in 15 cases (SUVmax 15.8 ± 4.2). The metabolic patterns included homogeneous uptake (13 cases), rim-like uptake (10 cases), and diffuse uptake (2 cases). CT morphology revealed round/oval lesions in 16 cases (64%, longest diameter 11.8 ± 4.5 cm), irregular lesions in 7 cases (28%, 17.6 ± 5.7 cm), and diffuse splenomegaly in 2 cases (8%, 18.4 ± 2.7 cm). Lesions demonstrated well-defined margins (4 cases) or ill-defined margins (21 cases), with central necrosis/cystic degeneration/hemorrhage (13 cases) or solid appearance (12 cases). Contrast-enhanced CT showed mild (7 cases, 28%), moderate (8 cases, 32%), and marked enhancement (9 cases, 36%). Pathological types included lymphoma (14 cases, mostly showing homogeneous hypermetabolism except 2 MALT lymphomas with hypometabolism), angiosarcoma (7 cases, all demonstrating rim-like uptake with with photopenia in the necrotic centers), other sarcomas (3 cases including 2 EBV-positive inflammatory follicular dendritic cell sarcomas with well-defined hypermetabolic lesions and 1 unclassified sarcoma with heterogeneous uptake), and solitary metastasis (1 case showing nodular hypermetabolism). PET/CT demonstrated significantly higher diagnostic sensitivity (84% vs. 68%, p = 0.012) and superior staging capability (28% vs. 12%, p = 0.027) compared to CT, the diagnostic sensitivity of PET/CT combined with enhanced CT was 96%.Conclusion18F-FDG PET/CT provides significant diagnostic and staging value for SMTS, with SUVmax and metabolic patterns improving diagnostic accuracy. The combination of PET/CT and pathological biopsy is recommended for optimal evaluation.